Justiça restaurativa : instrumento de efetivação do princípio constitucional da busca da felicidade : um estudo sobre a prática em Sergipe - Silva, Haroldo Luiz Rigo da (2017)
In the criminal sphere and the accountability of adolescents, there is an unprecedented crisis of the dominant paradigm, which requires, among other issues, a reformulation of prison politics and re-socialization, with the humanization of the process, so that a new path can be found that is sustained and that gives back to the Brazilian society re-socialized individuals and integrated to their communities. Restorative justice is announced as a new paradigm to challenge this crisis and presents a proposal for the sustainable construction of criminal procedures and prosecution of an infraction. This research investigates the importance of values and principles in the construction of the public policy of Restorative Justice and in this context seeks to know the stage in which is the Restorative practice in the area of Juvenile Criminal Law in the State of Sergipe. The study begins by identifying the conceptual, value, principles and methodological elements of Restorative Justice. It addresses the history of practice in order to critically identify the links of importance that help to see practice in the world, Latin America, Brazil and its evolutionary stage in the State of Sergipe, as well as to relate the main developments in practice in the State and the future steps that are projected in the next actions. In a third moment, it seeks to recognize what Juvenile Criminal Justice is about and then to propose a restorative lens under this branch of Law, assessing its actions in its three axes and its initial flow in practice in Sergipe. At the end, the constitutional discussion is held to recognize the frame through which one can see the restorative practice, with an approach to fraternal law, the principle of the dignity of the human person and the principle of the search for happiness.